Selected pathological, immunohistochemical and ultrastructural changes associated with an infection by Diphyllobothrium dendriticum (Nitzsch, 1824) (Cestoda) plerocercoids in Coregonus lavaretus (L.) (Coregonidae) - Dezfuli, B S (Journal of fish diseases, 2007)
The pathological changes induced by an infection of Diphyllobothrium dendriticum (Nitzsch, 1824) plerocercoids in powan, Coregonus lavaretus (L.), from Loch Lomond, Scotland, were assessed using immunohistochemical and ultrastructural techniques. In a sample of 26 powan, the occurrence of encysted plerocercoids of D. dendriticum on the outer surface of the stomach was 38.5% (n = 10) with the number of cysts ranging from 4 to 15 and measuring 4.2 +/- 1.0 mm x 3.4 +/- 0.9 mm (mean +/- SD). Histological examination of intestinal samples also revealed plerocercoids (2-21) encapsulated within a proliferation of mesenteric fibrous tissues of the gastric wall and, occasionally, by the gut lamina propria-submucosa and lamina muscularis. In section, cysts were tri-layered and were formed from a series of concentric whorls of fibroblast and collagen fibre-based connective elements. The extent of necrosis within each muscle layer and the serosa of the stomach differed, notably within the latter that was marked by a chronic inflammatory reaction and fibrosis. Within the cyst and around it, a large number of degranulating mast cell/eosinophilic granule cells were seen, in addition to melano-macrophage centres. Immunohistochemical staining of sections of infected stomach revealed a high density of elements, in close proximity to plerocercoids, staining positive for serotonin, bombesin, substance P and galanin. Uninfected material did not present the same levels of activity. Sections through both infected and uninfected tissue were also tested for elements containing vasoactive intestinal peptide, met-enkephalin, calcitonin gene-related peptide, neuropeptide Y and nitric oxide synthase, but these were absent